Intravital Imaging of Thrombosis Models in Mice - Kiouptsi, Klytaimnistra; Casari, Martina; Mandel, Jonathan; Gao, Zhenling; Deppermann, Carsten (Hämostaseologie, 2023)
Intravital microscopy is a powerful tool to study thrombosis in real time. The kinetics of thrombus formation and progression in vivo is studied after inflicting damage to the endothelium through mechanical, chemical, or laser injury. Mouse models of atherosclerosis are also used to induce thrombus formation. Vessels of different sizes and from different vascular beds such as carotid artery or vena cava, mesenteric or cremaster arterioles, can be targeted. Using fluorescent dyes, antibodies, or reporter mouse strains allows to visualize key cells and factors mediating the thrombotic processes. Here, we review the latest literature on using intravital microscopy to study thrombosis as well as thromboinflammation following transient middle cerebral artery occlusion, infection-induced immunothrombosis, and liver ischemia reperfusion.
Keywords: thrombosis; platelet; microscopy; intravital; mice